ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN LABA BERSIH PADA PERUSAHAAN - Beta Asteria (JURNAL MANAJEMEN, 2021)
This study aims to analyze the effect of the Current Ratio (CR) and Debt Equity Ratio (DER) on the Net Profit Margin of LQ 45 companies listed on the Indonesia Stock Exchange. The analysis was carried out partially and simultaneously using linear regression through the t test and F test. The sampling technique used was purposive sampling, there were 112 samples. Panel data is used in this study. Panel data is a combination of cross-sectional and time series data. There are 112. Cross-sectional data, there are 28 companies included in the sample criteria and time series data for 4 years. The results showed that partially Curent Ratio (CR) was not proven to have a significant effect on Net Profit Margin (NPM) while Debt Equity Ratio (DER) was proven to have a significant effect on Net Profit Margin (NPM). And simultaneously proved that the Current Ratio (CR) and Debt Equity Ratio (DER) proved to have a significant effect on the Net Profit Margin (NPM).